Export development of Russian regions under sanctions restrictions - S. S. Krasnykh (Вестник университета)
The relevance of this study is related to the need to search for drivers of growth in the socio-economic development of the regions of the Russian Federation in the context of a special military operation, since the current unprecedented sanctions restrictions aimed at the Russian economy are causing serious damage to it. Involvement in foreign trade relations, and in particular export, has a positive effect on the socio-economic development of the region. The article analyses the development of Russian regions exports and proposes a spatial model of exports using local and global Moran indices. The model allows us to determine clusters of high and low values ofthe studied indicator, growth poles, zones of influence of growth poles and a cluster of high values, and potential territories that can become export development centers of the Russian Federation in the future.